Picket notice at Chobham Farm Depot, 1972 (London, 1972)
1972 1970-74 "Picket notice at Chobham Farm Depot, 1972" [BW0081], 1972, Trades Union Congress In the early 1970s, there was unrest among dockers over the loss of work due to 'containerisation', with the packing and unpacking of containers being done at terminals outside the dock area. In the summer of 1972, the National Industrial Relations Court, set up under the 1971 Industrial Relations Act prohibited picketing at two East London container depots. This photo at the Chobham Farm container depot in Newham shows a picket notice reading "Warning, this depot is dock work. Keep out". The picketing continued and on 21 July, five of the dockers were committed for contempt and put in Pentonville Prison.